PRAKTIK DISKUSI SARASEHAN DENGAN PENDEKATAN COMMUNITY DEVELOPMENT - Anis Setiyanti (Misykat al-Anwar Jurnal Kajian Islam dan Masyarakat, 2022)
ABSTRACTPR IPM SMK Muhammadiyah 01 South Tangerang is a student institution based in SMK Muhammadiyah 01 South Tangerang. Since the Covid-19 pandemic has changed the climate of school life, this student institution has experienced difficulties in running its organizational wheels. The new habit pattern demands a change in the system and framework that has become the standard of work since the previous management periods. However, the adaptation of an organization, especially a student body, to the demands of new habit patterns is not an easy thing. The subgroup of Group 11 KKN UMJ 2021 took the initiative to provide education one method of discussion that is relevant to the characteristics of upper-middle-level students, namely discussion workshops. This program will be run through a technology-based community development approach, with direct practice methods through an online system. Through this community development approach, the program will be run in a participatory manner by proactively involving partners in every work agenda. The subgroup of Group 11 KKN UMJ 2021 will be the facilitator of this online workshop discussion practice, with the hope that through this program, PR IPM SMK Muhammadiyah 01 South Tangerang can get a new instrument that is useful in running the organization. Keyword: Workshop Discussion, Community Development, Direct Practice Method